Evaluation of Identification and Susceptibility for Candida Spp. Isolated Directly from Positive Blood Culture Bottles - Ândrea Celestino de Souza; Luciano Z. Goldani; Eliane Würdig Roesch; Larissa Lutz; Patricia Orlandi Barth; Paulo André de Souza Sampaio; Valério Rodrigues Aquino; Dariane Castro Pereira (International Journal of Microbiology)
Determination of the susceptibility profile of isolates of Candida from blood culture bottles is extremely important for correctly guiding patient pharmacotherapy. The aim of this study was to compare the results of analysis of Candida isolated directly from blood culture bottles by the VITEK MS MALDI-TOF identification system and the fluconazole disk diffusion assay with those of standard identification methods. Testing directly from the bottle allowed results 24 to 48 hours quicker than the standard method. There was a categorical agreement of 51.64% (47 of 91 samples) between the results of analysis directly from the bottle and analysis by the standard method. Regarding species identification, there was 96.15% agreement for Candida parapsilosis (25 of 26 samples). Categorical agreement between the rapid and standard disk diffusion methods was 95%, and the agreement between the rapid disk diffusion method and the broth microdilution method was 97%. Only minor errors in the rapid method were observed: 3 (5%) in the standard disk diffusion method and 2 (3%) in the broth microdilution method. Our study concluded that the rapid disk diffusion method for fluconazole is a fast, easy, reproducible, and consistent method. Its timely implementation for testing antifungal agents in the clinical microbiology laboratory can help reduce profile release times, thus helping to determine the most appropriate antifungal treatment.